Chemical Modification of Chitosan as An Adsorbent for The Removal of Dyes - Aishwarya Muralidharan Nair,; Devika K S,; Saraswathy Nachimuthu,; Ramalingam Ponnusamy,; Dymphan Gonsalves, (International Journal of Scientific Research in Science and Technology, 2025)
Chitosan beads were chemically modified by cross-linking with aldehydes such as valeraldehyde, octanal, o-phthalaldehyde and 9-phenanthrenecarboxaldehyde in order to obtain chitosan Schiff base beads. Chemically modified beads were characterized using FTIR, XRD and elemental analysis (C, H and N). Three cycles of adsorption and desorption studies were performed, modified beads were used for the removal of both Brilliant Blue and Methyl Orange dyes. The chitosan-Schiff base beads exhibited exemplary dye removal efficiency and maintained their ability throughout three cycles. The desorption study was performed using 70% ethanol as a desorbing agent, the desorption study revealed that the modified beads can be regenerated and can be employed as a favourable adsorbent industrially to remove acid dyes from wastewater.
Keywords: Chitosan; Modification; Schiff base; Aldehydes; Adsorption; Desorption